2019
DOI: 10.1017/s1537592719002597
|View full text |Cite
|
Sign up to set email alerts
|

Shut Up and Play: Black Athletes, Protest Politics, and Black Political Action

Abstract: The convergence of sports and celebrity can have a powerful influence on everyday politics, especially for groups underrepresented in mainstream American society. This article examines the relationship between race, celebrity, and social movements, specifically Colin Kaepernick’s protest of police violence and whether his activism mobilizes black Americans to political action. Using the 2017 Black Voter Project (BVP) Pilot Study, we explore African American political engagement in the 2016 election, a time dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…Due to stereotyping of Black athletes, they are often reprimanded by the public for advocating for political causes (Kaufman 2008). Importantly, however, there is evidence to suggest that Colin Kaepernick's protests were able to mobilize Black Americans to participate in politics at higher levels (Towler, Crawford, and Bennett 2019). This suggests that how individuals view Black people in the world of sports is similar to the divide between Black people and White people in society at large.…”
mentioning
confidence: 99%
“…Due to stereotyping of Black athletes, they are often reprimanded by the public for advocating for political causes (Kaufman 2008). Importantly, however, there is evidence to suggest that Colin Kaepernick's protests were able to mobilize Black Americans to participate in politics at higher levels (Towler, Crawford, and Bennett 2019). This suggests that how individuals view Black people in the world of sports is similar to the divide between Black people and White people in society at large.…”
mentioning
confidence: 99%
“…On the one hand, race and racial views have been linked to the response to individual athletes such as Colin Kaepernick. Towler et al (2020) found Kaepernick's activism served as a mobilizing force for African Americans. Intravia and colleagues found responses to a politically charged Nike ad featuring Kaepernick varied by race (Intravia et al, 2019).…”
Section: The Public's View Of Sports and Politicsmentioning
confidence: 99%
“…On the one hand, race and racial views have been linked to the response to individual athletes such as Colin Kaepernick. Towler, Crawford and Bennett (2020) found Kaepernick's activism served as a mobilizing force for African Americans. Intravia and colleagues found responses to a politically-charged Nike ad featuring Kaepernick varied by race (Intravia, Piquero, Piquero, and Byers 2019).…”
Section: The Public's View Of Sports and Politicsmentioning
confidence: 99%